2022
DOI: 10.35378/gujs.704371
|View full text |Cite
|
Sign up to set email alerts
|

Determination of The Best Injection Stretch Blow Molding Process Parameters in Polyethylene Terephthalate Bottle Service Performance

Abstract: Highlights• The top load strength of the final bottle was associated with the stretch rod movement • The panel (body) weight is directly and seriously affected by the preform surface temperature.• The final pressure and stretch rod also affected the body weight by bilateral interaction.• GRA results (except for Stress Crack Resistance) are greater than the general results of Taguchi.• The general result of Stress Crack Resistance with Taguchi is greater than GRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In terms of production technology, Lontos et al [ 6 ] found that with the delay of pre-blowing pressure relative to the stretching effect, more materials would gather in the lower area of the final product by studying the influence of stretching and blow molding combination on the wall thickness distribution of 1.5Lt PET bottles. Akkurt et al [ 7 ] used Taguchi method (TM), Grey Relational Analysis (GRA), and ECHIP to analyze the effects of preform temperature, stretching rod position, and final pressure, and optimized the performance parameters. In addition, the orientation and crystallinity of PET molecules are also the main factors that determine whether the mechanical properties of finished products are excellent [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of production technology, Lontos et al [ 6 ] found that with the delay of pre-blowing pressure relative to the stretching effect, more materials would gather in the lower area of the final product by studying the influence of stretching and blow molding combination on the wall thickness distribution of 1.5Lt PET bottles. Akkurt et al [ 7 ] used Taguchi method (TM), Grey Relational Analysis (GRA), and ECHIP to analyze the effects of preform temperature, stretching rod position, and final pressure, and optimized the performance parameters. In addition, the orientation and crystallinity of PET molecules are also the main factors that determine whether the mechanical properties of finished products are excellent [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%